Mixture characteristics of buton rock asphalt - H. Ali, Mohamed (2011)
The huge deposit of Buton Rock Asphalt (BRA) in Lawele of Buton Island, Indonesia, has not been utilized optimally. The less optimal usage was due to lack of knowledge on its characteristics. It is expected that there will be a shortage in petroleum bitumen, due to high price or limited sources of petroleum in the future. In this research, the bitumen used was penetration grade 80 /100 as control. Numerous bitumen tests were conducted in the laboratory to investigate the characteristic of BRA bitumen such as the penetration, softening point, and viscosity test. Only one aggregate gradation was considered under this investigation. An attempt was made to evaluate the mixture characteristics of BRA. The optimum bitumen content by using the Superpave mix design method were 6% , 6%, 6.5%, 7% for petroleum bitumen, BRA bitumen, 10% BRA granular and 15% BRA granular, respectively. Then by using Universal Testing Machine (UTM), the samples were tested for performance tests which were Indirect Tensile Stiffness Modulus Test and Dynamic Creep Test. The samples were tested at different temperatures of 30˚C, 40˚C, 50˚C using the Indirect Tensile Stiffness Modulus Test. Similarly, the samples were tested at 45˚C using Dynamic Creep Test. It was observed that the effectiveness of using BRA as granular showed better performance in the asphalt mixture. From the results, the use of 15% BRA granular showed the highest stiffness modulus and the highest permanent deformation resistance when compared with 10% of BRA granular and BRA bitumen. In addition, the use of 15% BRA granular showed the highest creep resistance.